Analysis of T cell receptor beta chain CDR3 size using RNA extracted from formalin fixed paraffin wax embedded tissue. Issue 10 (October 1997) - O'Shea, U; Wyatt, J I; Howdle, P D
Abstract : AIMS: To isolate RNA and DNA simultaneously from formalin fixed paraffin wax embedded tissue to assess the clonality of enteropathy associated T cell lymphomas and to analyse it in detail by a non-radioactive method of T cell receptor complementarity determining region 3 (CDR3) spectratyping. METHODS: DNA and RNA were isolated simultaneously from formalin fixed paraffin wax embedded tissue blocks and subjected to the polymerase chain reaction (PCR) and semi-nested reverse transcription PCR (RT-PCR), respectively. The RT-PCR T cell receptor V beta products were analysed by CDR3 spectratyping using a denaturing polyacrylamide gel and silver staining. RESULTS: Usable DNA and RNA were isolated simultaneously from formalin fixed paraffin wax embedded tissue. The specific clonality of the tissue was successfully analysed by a non-radioactive method of T cell receptor CDR3 spectratyping of the RT-PCR products. CDR3 spectratying of the RT-PCR products demonstrated the precise clonal nature of the tumour and non-tumour tissue showing that the non-tumour tissue comprised an oligoclonal population of a number of different T cell receptor V beta families. The tumour tissue comprised two T cell subtypes of the one family, T cell receptor V beta 9. CONCLUSIONS: RNA and DNA were isolated from formalin fixed paraffin wax embedded enteropathy associated T cell lymphoma tissue. Detailed analysis of clonality can be carried out by a non-radioactive method of CDR3 spectratyping.